Design, Synthesis, and Antitumor Biological Evaluation of Galaxamide and Its Analogs - Yanyan Guo; Huixia Fan; Zhiqiang Luo; Jian Yang; Guodu Liu (Molecules)
Galaxamide, an N-methylated cyclo-pentapeptide containing five D-leucines isolated from Galaxaura filamentosa, has shown significant antitumor activity. This unique cyclo-pentapeptide offered a fresh skeleton for structural modifications. Herein, galaxamide and its 23 analogs (Gala01~Gala24) were designed and synthesized by substituting D-leucine with various proteinogenic amino acids or altering the amino acid configuration using the “3 + 2” strategy, and the in vitro antitumor activity of these cyclopeptides was studied utilizing the CCK-8 assay against two human tumor cell lines (A549 and K562) and one human normal cell line (293T). The total yields of galaxamide and its analogs reached 9.7% and 9.1–16.0%, respectively. CCK-8 assays demonstrated that these compounds showed broad-spectrum antitumor activity, with Gala04 exhibiting outstanding activity against K562 cells (IC50 = 4.2 µM). The anticancer efficacy of galaxamide analogs against tumor cell lines was significantly influenced by the quantity of D-leucines and the D-leucine position.